List of the birds from Parque Luro Reserve, La Pampa (Semiárida, 2020)
A survey was made of birds from Parque Luro Reserve in La Pampa province. The Iist of species was based on extensive census, point counts along border to lagoon and strip transect carried out between 1995 and 2001. The species registred were 146 belonging to 42 families. The result show that 55 percent is permanent resident and Tyrannidae, Emberizidae and Furnariidae were the families more abundant specifically. During the period of the study 66 species breed in the reserve, 77 percent were resident and 23 percent were summer resident. The Tyrannidae family contributed wiht the major number of nesting species and nest due to the abundance of nest corresponding to Serpophaga griseiceps, Pyrocephalus rubinus and Elaenia parvirostris. We recorded Molothrus bonariensis as parasite of Zonotrichia capensis and Mimus saturninus.
Keywords: birds; la Pampa province; biodiversity; residence status; trophic preferences and nesting